The protection of ammonia-oxidizing bacteria (AOB) using PDDA/GO composite materials in high salinity wastewater. (October 2022) - Pei, Qianqian; Chen, Ming; Li, Jingda; Liu, Jie; Wu, Nan; Chen, Kaiyang; Chen, Xiaoyu; Liu, Yanli; Feng, Yifeng; Ren, Gaofeng; Liu, Xiaoying
Abstract: Ammonia oxidation is a critical process during nitrogen removal, while the activity of ammonia oxidizing bacteria (AOB) might be impacted severely in disposing high-salinity nitrogen-containing wastewater. To protect AOB in high saline medium, layer-by-layer self-assembly using graphene oxide (GO) and poly(diallyl dimethyl ammonium chloride) (PDDA) was applied to immobilize enriched AOB. By mixing GO and AOB, it was found that 30 mg/L GO showed the best promotion on the ammonia oxidation capacity of AOB. After coating, AOB with PDDA/GO showed higher absolute value of zeta potential of −20.1 ± 1 mV and compact structure. Comparing with uncoated AOB, although NH4 + -N consumption process was slightly inhibited by the PDDA/GO composite materials under low-salinity conditions (0–2 % NaCl), they presented great effective protection on the capacity of AOB in a 3 % NaCl solution. The consumption ratio of NH4 + -N was 1.34 times that of uncoated AOB, and the accumulation ratio of NO2 − -N of the former one was 1.40 times that of the latter. It inferred that the inhibitory to mass transferring caused by immobilizing materials was less than its positive promotion of AOB protection at 3 % NaCl concentration, and the protection of PDDA/GO composite materials was better than GO. This finding has some certain guiding significance for ammonia oxidation in high salinity. Graphical abstract: Unlabelled Image Highlights: GO concentration of 30 mg/L promoted the nitrosification activity of AOB. PDDA with positive charge was conducive to form compact structure with GO to coat AOB. PDDA/GO composite materials protected AOB from activity inhibition in 3 % salinity.